PARTIAL CHARACTERIZATION AND CLONING OF PROTEASE FROM BACILLUS - Ramakrishnan, Valya; Thambidurai, Yuvarani; Rajasekharan, Satish Kumar; Mohanvel, Sucharitha Kannappan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The present research focused on amplification of protease gene from Bacillus strain which was then assessed for maximal enzyme activity. Methods: A putative Bacillus strain was isolated from soil, inoculated into protease production media, and optimized with appropriate pH and temperature conditions for maximal enzyme activity. Genomic DNA was isolated from the strain and amplified the fragment by polymerase chain reaction (PCR) using gene-specific primers for protease. The fragment is then ligated into a T/A cloning vector and transformed into calcium chloride-treated competent Escherichia coli DH5Î± cells. The plasmids were then isolated and confirmed the presence of the gene. Results: A specific amplification of 1.1 kb was observed following PCR. The amplified product includes the coding sequence and a signal peptide sequence of the protease gene. After cloning with T/A cloning vector pTZ57R/T and transformed into E. coli DH5Î± competent cells, the recombinant plasmid was selected using blue-white selection. Plasmid DNA isolated from the recombinant strains and confirmed the presence of a gene of interest using PCR and quantified by an assay for maximal protease activity. The optimum pH was found to be 10.1 and giving an activity of 21.566 international unit (IU)/ml, and the optimum temperature was found to be on 60Â°C giving an activity of 38.708 IU/ml. Conclusion: Amplification of protease gene by PCR isolated from Bacillus strain and optimization of pH and temperature conditions for the assessment of subtilisin Carlsberg produced by it. Subtilisin which is protein engineered can be used in commercial products such as stain cutter, dishwashing detergents, cosmetics and food processing, and contact lens cleaner.